Association of Adding Aspirin to Warfarin Therapy Without an Apparent Indication With Bleeding and Other Adverse Events - Schaefer, Jordan K. (JAMA Intern Med, 2019)
IMPORTANCE: It is not clear how often patients receive aspirin (acetylsalicylic acid) while receiving oral anticoagulation with warfarin sodium without a clear therapeutic indication for aspirin, such as a mechanical heart valve replacement, recent percutaneous coronary intervention, or acute coronary syndrome. The clinical outcomes of such patients treated with warfarin and aspirin therapy compared with warfarin monotherapy are not well defined to date. OBJECTIVE: To evaluate the frequency and outcomes of adding aspirin to warfarin for patients without a clear therapeutic indication for combination therapy. DESIGN, SETTING, AND PARTICIPANTS: A registry-based cohort study of adults enrolled at 6 anticoagulation clinics in Michigan (January 1, 2010, to December 31, 2017) who were receiving warfarin therapy for atrial fibrillation or venous thromboembolism without documentation of a recent myocardial infarction or history of valve replacement. EXPOSURE: Aspirin use without therapeutic indication. MAIN OUTCOMES AND MEASURES: Rates of any bleeding, major bleeding events, emergency department visits, hospitalizations, and thrombotic events at 1, 2, and 3 years. RESULTS: Of the study cohort of 6539 patients (3326 men [50.9%]; mean [SD] age, 66.1 [15.5] years), 2453 patients (37.5%) without a clear therapeutic indication for aspirin were receiving combination warfarin and aspirin therapy. Data from 2 propensity score–matched cohorts of 1844 patients were analyzed (warfarin and aspirin vs warfarin only). At 1 year, patients receiving combination warfarin and aspirin compared with those receiving warfarin only had higher rates of overall bleeding (cumulative incidence, 26.0%; 95% CI, 23.8%-28.3% vs 20.3%; 95% CI, 18.3%-22.3%; P < .001), major bleeding (5.7%; 95% CI, 4.6%-7.1% vs 3.3%; 95% CI, 2.4%-4.3%; P < .001), emergency department visits for bleeding (13.3%; 95% CI, 11.6%-15.1% vs 9.8%; 95% CI, 8.4%-11.4%; P = .001), and hospitalizations for bleeding (8.1%; 6.8%-9.6% vs 5.2%; 4.1%-6.4%; P = .001). Rates of thrombosis were similar, with a 1-year cumulative incidence of 2.3% (95% CI, 1.6%-3.1%) for those receiving combination warfarin and aspirin therapy compared with 2.7% (95% CI, 2.0%-3.6%) for those receiving warfarin alone (P = .40). Similar findings persisted during 3 years of follow-up as well as in sensitivity analyses. CONCLUSIONS AND RELEVANCE: Compared with warfarin monotherapy, receipt of combination warfarin and aspirin therapy was associated with increased bleeding and similar observed rates of thrombosis. Further research is needed to better stratify which patients may benefit from aspirin while anticoagulated with warfarin for atrial fibrillation or venous thromboembolism; clinicians should be judicious in selecting patients for combination therapy.